(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Infections that are established 30 days after operation or contained within a year among people who have implants at or near the surgical site are referred to as surgical site infections (SSIs). About 2% of surgical complications are considered surgical site infections, and they present about 20% of healthcare-related infections. Previous studies discovered that there are not enough levels of knowledge and awareness regarding surgical site infections in Saudi Arabia. Therefore, determining knowledge and awareness of SSI can be helpful in developing preventive measures that will reduce complications, hospital stays, and readmission rates that are associated with surgical site infections (SSI). This study aimed to assess the knowledge level among the Saudi population About the risk of Surgical Site Infection. Methods: A cross-sectional study was conducted among the Saudi population in 2024. The questionnaire was covering socio-demographic information, clinical characteristics, and knowledge and awareness of SSIs. Data analysis was performed using SPSS to determine the level of knowledge and awareness among the population. Results: Regarding knowledge and awareness levels of surgical site infections (SSIs), only 37.2% out of 575 participants correctly defined SSIs as infections of both skin and deep organs, while 61.6% had never heard of them. A majority of participants (91%) believe SSIs are preventable, with 41.6% citing wound cleanliness and 38.2% emphasizing hand hygiene as key measures; however, only 3.8% exhibited high knowledge and 19.0% had high awareness levels. Notably, 84.7% had not received any educational materials about SSIs, and 81.4% reported that healthcare workers did not discuss SSIs with them prior to surgery. Despite this lack of awareness, a considerable 94.8% affirmed SSIs can be treated, recognizing interventions like drainage and debridement as important. Conclusion: The study highlighted a critical gap in awareness and knowledge of surgical site infections (SSIs) among the Saudi population, the findings indicate that a substantial majority had not received adequate educational resources on SSIs or were engaged in discussions concerning preventive measures prior to surgery. Given the significant implications of SSIs on patient outcomes, healthcare costs, and overall surgical morbidity, there is an urgent need for targeted community-based education programs. Such initiatives should focus on increasing awareness and understanding of SSIs, thereby empowering patients to contribute actively to their own surgical care and potentially reducing the incidence of these infections in the future.